ELECTROCHEMICAL OXIDATION AND DETERMINATION OF AN ANTI-CANCER DRUG PEMETREXED DISODIUM - DEVARUSHI, UMESH S; Shetti, Nagaraj P; TUWAR, SURESH M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Abstract-The electrochemical oxidation of an anti-cancer drug Pemetrexed disodium has been investigated at glassy carbon electrode using voltammetric techniques. The dependence of current on potential, pH, concentrartion, scan rate, and excipients were investigated to optimize the experimental conditions. According to the liner relation between peak potential, peak current, scan rate and Pemetrexed disodium concentration, differential pulse voltammetric method for the quantitative determination in phosphate Buffer solution was developed. The linear response was obtained in the range of 10 ÂµM to 0.75 ÂµM with a detection limit of 0.19 ÂµM. The electrochemical oxidation of mechanism of an anti-cancer drug Pemetrexed disodium was proposed. Â Keywords- Pemetrexed disodium, Cyclic Voltammetry, Electochemical Studies, Glassy carbon electrode